Investigation of Heavy Metal Bioaccumulation in the Nervous System, Skin and Skeletal Tissues of Wastewater-Fed Fish - Aslihan Katip (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
Treated urban wastewater fish are used in fish farming in some countries around the world. However, it can be dangerous to fish and people consuming it due to toxic chemicals and microbial pollution. In this study, the effects of heavy metals (Ag, Al, As and B) on the nervous system, skeletal and skin tissues of fish, and the accumulation in these tissues of fish fed in a wastewater treatment plant with secondary treatment are explained as an example. Ag, Al, As and B in treated effluent and skeleton, skin, eyes and brain tissues of Carassius gibelio species were investigated seasonally. According to annual averages the size order of Ag and B concentrations were skeleton> skin> eyes>brain and skeleton> skin>brain>eye respectively. Also, skin>brain>eyes>skeleton was for As and Al. TF (Transfer Factor) values of all metals examined were determined as >1 in the four tissues and the metals caused bioaccumulation because of treated effluent. The size order of TF and BCF (Bio-concentration Factor) values in skin and eye tissue were the same and it was Ag>Al>As>B. It was Ag>Al>As>B in skeleton, Al>As>Ag>B in brain. HQ (Hazard Quotient) of Al in all tissues had carcinogenic risk level.